Microsurgical anatomy and approaches to thalamic gliomas. Part 1: A cartography guide for navigating to the thalamus. Integrating 3D model rendering with anatomical dissections - Martínez Santos, Jaime L; Aljuboori, Zaid; Richardson, Angela M; Hanalioglu, Sahin; Peker, Halil Olgun; Aydin, Ilhan; Al-Sharshahi, Zahraa F; Tunc, Osman; Karatas, Derya; Avci, Emel; Baskaya, Mustafa K (Journal of neurosurgery, 2024)
The selection of appropriate microsurgical approaches to treat thalamic pathologies is currently largely subjective. The objective of this study was to provide a structured cartography map for surgical navigation to treat gliomas involving different surfaces of the thalamus. Fifteen formalin-fixed, silicone-injected cadavers (30 sides) were dissected, and 10 adult brain specimens (20 sides) were used to illustrate thalamic microsurgical anatomy using the Klingler fiber dissection technique. Exposures and trajectories for the six most common microsurgical approaches were depicted using MR data from healthy subjects converted into surface-rendered 3D virtual brain models. Additionally, thalamic surfaces exposed with all six approaches were color mapped on the virtual 3D model and compared side-by-side in 360° views with previously reported microsurgical approaches. These 3D models were then used in conjunction with topographic data to guide cadaveric dissection steps. There are two general surgical routes to thalamic lesions: the subarachnoid transcisternal and transcortical routes. The transcisternal route consists of the following three approaches: 1) anterior interhemispheric transcallosal approach, which exposes the anterior and superior thalamus; 2) posterior interhemispheric transcallosal approach, which exposes the posterosuperior thalamus; and 3) supracerebellar infratentorial approach, which exposes the posteromedial cisternal thalamus and can be extended laterally to approach the posterolateral thalamus by cutting the tentorium. The three transcortical approaches are the 1) superior parietal lobule approach, which exposes the posterosuperior thalamus and is particularly advantageous in the setting of hydrocephalus; 2) transtemporal gyrus approach, which exposes the inferolateral thalamus; and 3) transsylvian transinsular approach, which exposes the lateral thalamus (slightly more superiorly and posteriorly) and is advantageous for pathologies extending laterally into the peduncle, lenticular nucleus, or insula. Microsurgical approaches to thalamic gliomas continue to be challenging. Nonetheless, safe and effective cisternal, ventricular, and cortical corridors can be developed with thoughtful planning, anatomical understanding, and knowledge of the advantages, risks, and limitations of each approach. In some cases, it is wise to combine these approaches with staged procedures, as the authors demonstrate in Part 2. In Part 1 of this two-part series, they discuss thalamic microsurgical anatomy and illustrate the trajectory and exposures of all six approaches to guide decision-making. Part 2 discusses their thalamic glioma microsurgical case series, which utilizes these microsurgical approaches.